The Development Critical Thinking by Using Visualize Media in the Project Approach at Sathid Kindergarten of Luang Prabang Teachers Training College - PHANTHONG, Bounlai (Souphanouvong University Journal Multidisciplinary Research and Development, 2025)
This experimental study examined the development of critical thinking skills through the use of visual media in the Project Approach among Kindergarten 2 students at Sathid Kindergarten, Luang Prabang Teachers Training College, during the 2024–2025 academic year. The objectives were to assess students’ critical thinking skills and compare them before and after the implementation of visual media in project-based learning. Using Krejcie and Morgan’s sample size determination table, a sample of 28 students (12 girls) was selected. The study involved the preparation of instructional materials, visual media, and teaching aids. A 10-question pre-test (30 minutes) was administered prior to the intervention. Nine Project Approach lesson plans were implemented, with observations and recordings of student behaviors. Project activities were assessed using established evaluation criteria, followed by a post-test of the same format. The findings showed a high level of critical thinking development, with a mean score of 7.33 and a standard deviation of 0.30. Overall, critical thinking across specific domains was at a moderate level (mean = 1.87, SD = 0.57, 62.34%). Among the individual components, evaluation skills had the highest mean, followed by practical application, method selection, and problem identification, which had the lowest. Critical thinking performance showed a consistent upward trend across the sessions, with percentages of 33.33%, 41.67%, 50.00%, 55.56%, 50.00%, 77.78%, 80.56%, and 86.11% in the final two sessions. A comparison of pre- and post-test results indicated a statistically significant improvement in critical thinking skills after the use of visual media in Project Approach instruction (p < .05).